The structure of physical fitness and its correlation analysis at young players aged 16-17 years at the stage of basic training - A.N. POPOV (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : The questions about the importance of physical fitness of young players to improve the management and correction of the training process. Material : In the research participated 40 players aged 16-17 years of specialized youth football school of FC "Obolon-Brewery". Data for the study of physical fitness were teacher observations and teacher testing carried out under the direct training of young players. Results : It is shown that the structure of physical fitness among all the studied parameters there is a close correlation relationship, except for a parameter that characterizes the start speed. It was found that the above regularities indicate the advisability of excluding the studied parameters in the structure of physical fitness of young players to improve the efficiency of the training process at the base of specialized training. Conclusions : It is recommended to improve the starting speed to use non-gaming and technical and tactical exercises.